Basic Principles and Practice in Surgery - Gabriela Pop, Miana (IntechOpen, 2019)
This publication aims to support young doctors and surgery residents during their training period. A surgical residency is a crucial period for a young doctor. A great volume of theoretical information along with difficult and demanding practical skills need to be acquired in a relatively short period of time. This book is a tool for rapid, correct acquisition of elementary surgical notions and techniques, which are the basis for the training of today's surgery resident.